2022
DOI: 10.3390/agronomy12112668
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Preferred Genotype Traits and Socio-Economic Factors Influencing the Adoption of Improved Cowpea Varieties in South-Central Niger

Abstract: Cowpea, Vigna unguiculata (L.) (Walpers, 1842), is an important legume for food and nutrition security, and income generation. Despite decade-long efforts to disseminate improved varieties, cowpea productivity remains low in Niger. This is due, in part, to the limited adoption of improved cowpea varieties among farmers. Increasing the adoption of improved cowpea varieties requires a better understanding of farmers’ preferred genotype traits and socio-economic factors that influence their decision. We interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…As observed in Table 2 , most farmers selected grain yield (83.33%), but was preferred by slightly more women (87%) than men (79%). Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…As observed in Table 2 , most farmers selected grain yield (83.33%), but was preferred by slightly more women (87%) than men (79%). Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women.…”
Section: Discussionsupporting
confidence: 61%
“…Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women. From the study, the finding that more women preferred pods that grow above the canopy for the reason that such cowpea are easier to harvest confirms ( Ridgeway, 2009 ; Sylla et al, 2023 ) that gender relations fit into social structures that define agricultural tasks.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…For cowpeas, the Maradi region accounts for about half (48.6%) of all certified seeds available in the country, while the Zinder region only represents 5.6% [14]. However, these improved varieties have low average adoption rates in both regions, ranging from 3.3 to 38.0% [15]. The cost of seeds can be a barrier to adoption among smallholder farmers with limited financial resources.…”
Section: Introductionmentioning
confidence: 99%